RELATIONSHIP BETWEEN DEPRESSION LEVELS AND THE ABILITY OF DAILY ACTIVITIES OF THE ELDERLY IN SABAI NAN ALUIH SICINCIN SOCIAL RESIDENCE - SYAHRUL; AULIA, FAJRI FEBRINI; KASMORA, DEPERMAN (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2025)
Physical and psychological function decline often occurs when entering old age or also called elderly. The most common psychological problem faced by the elderly is depression. This disorder can interfere with daily activities. The purpose of this study was to determine the relationship between depression levels and the ability to carry out daily activities in the elderly at the Sabai Nan Aluih Sicincin Social Home. This type of research is quantitative with an analytical research method with a Cross-sectional approach. This research was conducted at the Sabai Nan Aluih Sicincin Social Home in July 2024. Sampling was carried out using a random sampling technique with a sample size of 52 respondents. Data collection tools using questionnaires. Data analysis using the Chi Square test at the 5% level. Based on the research results obtained from respondents, 34 people (65.4%) had mild depression, 26 people (50.0%) had independent basic activity abilities. The results of the chi square analysis showed a p-value = <α = 0.05) which indicates a relationship between the level of depression and the ability of basic activities in the elderly at the Sabai Nan Aluih Sicincin Social Home. The conclusion is that there is a relationship between the level of depression and the ability of basic activities in the elderly at the Sabai Nan Aluih Sicincin Social Home. Suggestions for the administrators of the social home to provide counseling to the elderly regarding psychological management to avoid depression